Implementation of Quality Models in the Third Sector in Spain - Alfonso Conde Lacárcel (European Scientific Journal, ESJ, 2018)
The Third Sector of Social Action in Spain has been the object of numerous studies. These studies were conducted in order to discover its reality and to favor its visibility and for the permanent improvement of the work processes with different groups generally at risk of exclusion. In 2015, the data provided by the Social Action N.G.O Platform and the Third Sector Platform at the national level indicated numerous difficulties which were to be resolved, including the adequate development of quality management systems. At the same time, the results of a research thesis were presented in the city of Granada so as to discover the level of implementation of quality management systems in N.G.Os, N.P.Os, and associations of the First Level. We followed a methodology of mixed research with the use of questionnaires and interviews on a sample focused on offering community and educational services in nonformal education. After reviewing different aspects, this document presents the continuation of this thesis of research in this occasion at national level. It also aims to complete the panorama that was initiated and was offered to the different administrations and organizations, information for the improvement of its educational management and intervention processes, and equating the fundamental rights of Spanish society. The expected results will require the development of different initiatives for the implementation of quality management models adapted to each area of intervention, following models already combined in European countries, including the Great Britain.